Sustainable Urban Tourism Strategy in Ubud, Bali: Integration of Infrastructure and the Principles of Tri Hita Karana - Putu Gede Islandy Sentosa; Nyoman Diah Utari Dewi; Ni Putu Tirka Widanti (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Abstract Bali's tourism in 2025 recorded a record 7.05-7.12 million international visitors, the highest in a decade, with Ubud as the spiritual cultural center bearing an estimated 2 million annual visitors. However, overtourism triggered crises: 30-35% rice field conversion (350 Ha), Ubud main road congestion 12 hours/day (75 dB noise pollution), seasonal flooding 15 days/year, and 90 tons/day plastic waste (18% Bali total). Ubud infrastructure scored only 3.4/10, contrasting with Lodtunduh adat village's 8.7/10. This qualitative case study used data triangulation: 15 in-depth interviews (banjar leaders, Gianyar Tourism Office, homestay entrepreneurs), 72-hour participatory observation, and document analysis (Gianyar RTRW 2025-2030, banjar reports). The research developed the first THK-Infrastructure Matrix, an innovative tool operationalizing Bali's Tri Hita Karana philosophy (Parahyangan-Pawongan- Palemahan) for modern infrastructure evaluation. Four key findings from Miles & Huberman thematic analysis: rice field conversion highest priority, noise disturbing temple spirituality, concrete drainage collapse, and plastic waste fracturing social harmony. Hybrid strategy adapted Lodtunduh best practices (adat zoning regulations, subak drainage, Rp5,000 local shuttles) with modern technology: Gianyar THK Zoning Regulation 2026 includes car-free zones 500m radius of 15 temples, 30% local homestay quotas, 350 Ha subak conversion moratorium, and 80 Ha hybrid bio-swale drainage. The model increases carrying capacity +28% while preserving cultural authenticity. Implementation recommendations: Public- Private-Banjar Partnership (Tourism Office Rp5B, banjar Rp2B, private Rp10B) with THK Dashboard real-time monitoring system. Global contribution: Urban Cultural Resilience blueprint replicable to 500 worldwide overtourism destinations (Yogyakarta, Kyoto, Luang Prabang). Keywords: Sustainable Tourism, Tri Hita Karana, Ubud infrastructure, Ubud overtourism